Immunomodulatory effects of two recombinant arginine kinases in Sarcoptes Scabiei on host peripheral blood mononuclear cells - Xu, Yanting; Xu, Ziyi; Gu, Xiaobin; Xie, Yue; He, Ran; Xu, Jing; Jing, Bo; Peng, Xuerong; Yang, Guangyou (Frontiers in Immunology, 2022)
Background: As an important zoonotic parasitic disease with global distribution, scabies causes serious public health and economic problems. Arginine kinase (AK) is involved in cell signal transduction, inflammation, and apoptosis. Two AKs were identified in Sarcoptes scabiei, but their functions in the host immune response remain unclear. Methods: rSsAK-1 and rSsAK-2 were expressed, purified, and immunolocalized. The effects of rSsAK-1 and rSsAK-2 on rabbit PBMC proliferation, apoptosis, and migration; Bcl-2, Bcl-xl, Fas, Bax, and NF-κB transcription levels; and IL-2, IFN-γ, IL-4, IL-10, TGF-β1, and IL-17 secretion were detected. Results: rSsAK-1 and rSsAK-2 were cloned and expressed successfully. Both enzymes were ~57 kDa and contained 17-kDa tagged proteins, and had good catalytic activity and immunoreactivity. The proteins were located in the S. scabiei exoskeleton, chewing mouthparts, legs, stomach, and intestine. SsAK-1 and SsAK-2 were secreted in the pool and epidermis of the skin lesions, which may be involved in S. scabiei–host interaction. rSsAK-1 and rSsAK-2 significantly promoted cell proliferation, induced cell migration, inhibited apoptosis, and increased Bcl-2, Bcl-xl and NF-κB (p65) transcription levels concentration-dependently, and inhibited IL-2, IFN-γ, and IL-10 secretion and promoted IL-4 and IL-17 secretion. Conclusion: rSsAK-1 and rSsAK-2 might increase Bcl-2 and Bcl-xl expression by activating the NF-κB signaling pathway to promote cell proliferation and inhibit apoptosis, which induced PBMC survival. By inducing PBMC migration to the infection site, rSsAK-1 and rSsAK-2 shifted the Th1/Th2 balance toward Th2 and changed the Th17/Treg balance, which indicated their immune role in S. scabiei allergic inflammation.